Effect of Resilience Enhancement Program for First Year Nursing Students of Phrapokklao Nursing College, Chanthaburi - Bualuang, Thanyaporn; Tokun, Pimrat; Anan, Kamolnicha; Chaopipat, Yuree (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this quasi-experiment was to examine the efficiency of the enhancing resilience program for first year nursing students of Phrapokklao Nursing College, Chanthaburi. This quasi-experiment was categorized the selected students into two groups: the experimental group thirty persons and control group thirty persons. The experimental group received the enhancing resilience program in every week of six weeks. On the other hand, the control group got the suggestion and studied the resilient documents by themselves. The experimental tool was comprised of the enhancing resilience program and resilient evaluation form. The instruments as assessed reliability of 0.95 demonstrated an acceptable level of reliability. Data were analyzed by Pair t-test and Independent t-test. This study showed that the experimental group had more significantly resilient before they got this program. Moreover, the experimental group had more significantly resilient than the control group.